Evaluation of Fibrinolytic Capacity in Plasma during Thrombolytic Therapy with Single (scu-PA) or Two-chain Urokinase Type Plasminogen Activator (tcu-PA) by a Combined Assay System for Urokinase Type Plasminogen Activator Antigen and Function - Wojta, Johann; Binder, Bernd R; Huber, Kurt; Hoover, Richard L (Thrombosis and Haemostasis, 1989)
A combined assay for urokinase type plasminogen activator (u-PA) activity and antigen determination in plasma samples is described. This assay is based on binding of u-PA to an antibody immobilized on a microtiter plate followed by determination of the enzymatic activity of the bound u-PA. Thereafter bound u-PA antigen can be quantified by means of a specific peroxidase labelled monoclonal antibody against u-PA. By use of this assay system u-PA activity and antigen can be determined with lower detection limits of 0.08 IU/ml and 1.0 ng/ml, respectively, and intraassay as well as interassay coefficients of variation of 10% and 12% for activity and 5% and 7% for antigen determinations, respectively. Normal plasma levels of u-PA antigen could be determined to be 1.88 nglml ± 0.61. Furthennore, this assay system allows specific quantification of u-PA antigen and activity during thrombolytic therapy.
Keywords: u-PA ELISA; u-PA activity; Monoclonal antibodies; scu-PA; Thrombolytic therapy monitoring